Functional Connectivity of Hippocampal CA3 Predicts Neurocognitive Aging via CA1–Frontal Circuit. (2nd April 2020) - Liang, Xia; Hsu, Li-Ming; Lu, Hanbing; Ash, Jessica A; Rapp, Peter R; Yang, Yihong
Abstract: The CA3 and CA1 principal cell fields of the hippocampus are vulnerable to aging, and age-related dysfunction in CA3 may be an early seed event closely linked to individual differences in memory decline. However, whether the differential vulnerability of CA3 and CA1 is associated with broader disruption in network-level functional interactions in relation to age-related memory impairment, and more specifically, whether CA3 dysconnectivity contributes to the effects of aging via CA1 network connectivity, has been difficult to test. Here, using resting-state fMRI in a group of aged rats uncontaminated by neurodegenerative disease, aged rats displayed widespread reductions in functional connectivity of CA3 and CA1 fields. Age-related memory deficits were predicted by connectivity between left CA3 and hippocampal circuitry along with connectivity between left CA1 and infralimbic prefrontal cortex. Notably, the effects of CA3 connectivity on memory performance were mediated by CA1 connectivity with prefrontal cortex. We additionally found that spatial learning and memory were associated with functional connectivity changes lateralized to the left CA3 and CA1 divisions. These results provide novel evidence that network-level dysfunction involving interactions of CA3 with CA1 is an early marker of poor cognitive outcome in aging.